Biodiversity Governance for Managing Endemic and Threatened Medicinal Plants in India - A Geoinformatic Approach with Special Reference to Kalakad Mundanthurai Tiger Reserve, Southern Western Ghats of Tamil Nadu, India - Bisht, N. S. (Indian Forester, 2013)
No Abstract